OPTIMIZATION OF THE ROLE OF MOSQUES IN EMPOWERING THE COMMUNITY (CASE STUDY OF THE KAPAL MUNZALAN MOSQUE IN PONTIANAK INDONESIA) - Suhra Wardi; Willem Jansen (J-MD Jurnal Manajemen Dakwah, 2024)
Mosques are the center of Islamic civilization in the world. So in case of management, every mosque administrator must have competence and broad insight of management. So that the mosque functions as it was used during the time of the Prophet Muhammad, namely that the mosque was used as a place for social activities and was used for worship. This article describes the optimization of the function of the Kapal Munzalan Mosque in Pontianak as a center for community empowerment activities. The purpose of this research is to describe the role of mosque management in improving community welfare. This research uses a descriptive qualitative method (Krippendorff, 1993) to develop various programs for the improvement of the welfare of Muslims and library studies. Research results show that among the Ziswaf (Zakat, Infaq, and Shadaqoh) programs are as follows: leading businesses from Ziswaf funds, managed in the form of the Rice Infaq Movement (GIB) for pesantren and the poor, da'wah programs: nurturing and serving converts in rural areas, assisting mosques with knowledge and skills related to mindset, concepts, and management of prosperous, abundant mosques, through service programs; research, training, consultation, and networking, providing education and training in Digital Marketing & Digital Content, establishing Baitulmaal. This Baitulmaal is named Baitulmaal Munzalan Indonesia (BMI) and has 32 branches spread throughout Indonesia. Keywords: Empowerment, Mosque, Optamalization